Genetic analysis and identification of SSR markers associated with rice blast disease in a BC2F1 backcross population - Hasan, Nor' Aishah; Yusop, Mohd Rafii; Abdul Rahim, H.; Syd Ali, Nusaibah; Mazlan, Norida; Abdullah, Shamsiah (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2017)
Rice (Oryza sativa L.) blast disease is one of the most destructive rice diseases in the world. The fungal pathogen, Magnaporthe oryzae, is the causal agent of rice blast disease. Development of resistant cultivars is the most preferred method to achieve sustainable rice production. However, the effectiveness of resistant cultivars is hindered by the genetic plasticity of the pathogen genome. Therefore, information on genetic resistance and virulence stability are vital to increase our understanding of the molecular basis of blast disease resistance. The present study set out to elucidate the resistance pattern and identify potential simple sequence repeat markers linked with rice blast disease. A backcross population (BC2F1), derived from crossing MR264 and Pongsu Seribu 2 (PS2), was developed using marker-assisted backcross breeding. Twelve microsatellite markers carrying the blast resistance gene clearly demonstrated a polymorphic pattern between both parental lines. Among these, two markers, RM206 and RM5961, located on chromosome 11 exhibited the expected 1:1 testcross ratio in the BC2F1population. The 195 BC2F1 plants inoculated against M. oryzae pathotype P7.2 showed a significantly different distribution in the backcrossed generation and followed Mendelian segregation based on a single-gene model. This indicates that blast resistance in PS2 is governed by a single dominant gene, which is linked to RM206 and RM5961 on chromosome 11. The findings presented in this study could be useful for future blast resistance studies in rice breeding programs.